Anaerobic pre-treatment of pharmaceutical wastewater using packed bed reactor - Chelliapan, S.; Yuzir, A.; Md. Din, M. F.; Sallis, P. J. (International Association of Computer Science and Information Technology (IACSIT), 2011)

(untitled)
Effluents from manufacturing operations in the pharmaceutical industry, such as antibiotic formulation, usually contain recalcitrant compounds. An approach towards appropriate technology for the treatment of pharmaceutical wastewaters has become imperative due to strict water quality legislation for environmental protection. Typically, pharmaceutical wastewater is characterized by high chemical oxygen demand (COD) concentration, and some pharmaceutical wastewaters can have COD as high as 80,000 mg.L-1. Due to high organic content, anaerobic technology is a promising alternative for pharmaceutical wastewater treatment. Consequently, in the present study, an anaerobic packed bed reactor was employed to treat highly polluted pharmaceutical wastewater. The effect of organic loading rate (OLR) was assessed by adjusting feed substrate concentration and hydraulic retention time (HRT). The reactor performance was characterized in terms of chemical oxygen demand (COD) removal, volatile fatty acid (VFA), gas production, methane yield and pH. At an average reactor OLR of 1.58 kg COD.m-3.d-1 (HRT 5.6 d), the average soluble COD reduction was 73%. However, when the OLR was increased to 2.21 and 4.66 kg COD.m-3.d-1 the COD removal efficiency decreased gradually until 60 - 70% soluble COD removal was observed. Further increase of the OLR resulted in only around 53% soluble COD removal (average) was observed at an OLR of 5.71 kg COD.m-3.d-1, signifying as OLR was increased; the increasing load of complex pharmaceutical wastewater may have affected the methanogens.